(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2022)
The purpose of this paper is to draw attention to the initiatory (mystagogic) function of religion, which is associated with its essential spiritual (salvific) function. The text comprises three parts. The first one addresses the problems concerning the very definition of the phenomenon of religion, the attempts to formulate its definitions, either substantive (reflecting the essence of religion) or functional (emphasizing the functions of religion), and the issue of their empirical verification. In the second part, the various functions of religion are outlined in light of the distinction between essential and auxiliary functions (specifically and non-specifically religious). One of these is the initiatory (mystagogic) function, the verification of which takes place in the affective cognition of God. The third part characterizes the affective cognition of God, which originates in the affective states and leads to a deeper knowledge of the Absolute.